HAWK and HARRIER: Phase 3, Multicenter, Randomized, Double-Masked Trials of Brolucizumab for Neovascular Age-Related Macular Degeneration - Dugel, Pravin U; Koh, Adrian; Ogura, Yuichiro; Jaffe, Glenn J; Schmidt-Erfurth, Ursula; Brown, David M; Gomes, Andre V; Warburton, James; Weichselberger, Andreas; Holz, Frank G (Ophthalmology (Rochester, Minn.), 2020)
Two similarly designed phase 3 trials (HAWK and HARRIER) compared brolucizumab, a single-chain antibody fragment that inhibits vascular endothelial growth factor-A, with aflibercept to treat neovascular age-related macular degeneration (nAMD). Double-masked, multicenter, active-controlled, randomized trials. Patients (N = 1817) with untreated, active choroidal neovascularization due to age-related macular degeneration in the study eye. Patients were randomized to intravitreal brolucizumab 3 mg (HAWK only) or 6 mg or aflibercept 2 mg. After loading with 3 monthly injections, brolucizumab-treated eyes received an injection every 12 weeks (q12w) and were interval adjusted to every 8 weeks (q8w) if disease activity was present; aflibercept-treated eyes received q8w dosing. The primary hypothesis was noninferiority in mean best-corrected visual acuity (BCVA) change from baseline to Week 48 (margin: 4 letters). Other key end points included the percentage of patients who maintained q12w dosing through Week 48 and anatomic outcomes. At Week 48, each brolucizumab arm demonstrated noninferiority to aflibercept in BCVA change from baseline (least squares [LS] mean, +6.6 [6 mg] and +6.1 [3 mg] letters with brolucizumab vs. +6.8 letters with aflibercept [HAWK]; +6.9 [brolucizumab 6 mg] vs. +7.6 [aflibercept] letters [HARRIER]; P < 0.001 for each comparison). Greater than 50% of brolucizumab 6 mg-treated eyes were maintained on q12w dosing through Week 48 (56% [HAWK] and 51% [HARRIER]). At Week 16, after identical treatment exposure, fewer brolucizumab 6 mg-treated eyes had disease activity versus aflibercept in HAWK (24.0% vs. 34.5%; P = 0.001) and HARRIER (22.7% vs. 32.2%; P = 0.002). Greater central subfield thickness reductions from baseline to Week 48 were observed with brolucizumab 6 mg versus aflibercept in HAWK (LS mean -172.8 μm vs. -143.7 μm; P = 0.001) and HARRIER (LS mean -193.8 μm vs. -143.9 μm; P < 0.001). Anatomic retinal fluid outcomes favored brolucizumab over aflibercept. Overall, adverse event rates were generally similar with brolucizumab and aflibercept. Brolucizumab was noninferior to aflibercept in visual function at Week 48, and >50% of brolucizumab 6 mg-treated eyes were maintained on q12w dosing interval through Week 48. Anatomic outcomes favored brolucizumab over aflibercept. Overall safety with brolucizumab was similar to aflibercept (ClinicalTrials.gov; NCT02307682, NCT02434328).